ANALYSIS OF JUDGES' RATIO DECIDENDI IN ONLINE GAMBLING CRIMINAL DECISIONS USING CRIMINAL CODE PROVISIONS - Maria Christina; Prija Djatmika; Abdul Madjid (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Advances in information technology have driven the transformation of conventional gambling into gambling conducted through electronic systems. This situation has raised legal issues regarding the application of criminal law to online gamblers, particularly concerning the use of the Criminal Code (KUHP) or the Electronic Information and Transactions Law (UU ITE). The purpose of this study is to analyze the judges' ratio decision in criminal judgments involving online gambling that apply provisions of the Criminal Code (KUHP). The research method used is legal research with a statutory regulatory approach and a case approach. Based on the research conducted, it is evident that there are differences in the judges' reasoning regarding the classification of online gambling. In verdict number. 32/Pid.Sus/2025/PN Lmj, the Panel of Judges applied Article 27(2) in conjunction with Article 45(3) of the ITE Law, primarily on the grounds that the use of electronic systems and access to gambling websites fulfilled the element of making electronic information containing gambling content accessible, thereby rendering the ITE Law applicable as lex specialis. Conversely, in verdict number 41/Pid.B/2025/PN Pdp, the Panel of Judges applied Article 303 bis of the Criminal Code because the defendant acted solely as an online gambler and was not proven to have distributed, transmitted, or made electronic information containing gambling content accessible to others. This discrepancy highlights differing interpretations of the elements within the ITE Law, which impact legal applications. Therefore, consistency in legal interpretation and application